1981
DOI: 10.1007/bf00561949
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of propranolol stereoisomers in hyperthyroid patients

Abstract: The disposition of propranolol stereoisomers after administration of a single oral dose of the racemic drug was investigated in seven hyperthyroid patients before and after antithyroid drug therapy. The possibility of hypersensitivity to propranolol in the patients was evaluated by constructing plasma propranolol concentration -- beta-blocking effect curves. There was no statistically significant difference in elimination half-life (t1/2) between (+/-)- and (-)-propranolol before and after antithyroid drug the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1982
1982
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…However, the effect of hyperthyroidism on the clearance of single oral doses of propranolol is less clear. As indicated above, the earlier studies of Bell et aL (1977) and Rubenfeld et aL (1978) did not detect any change, and indeed this has also been the conclusion of a number of other workers (Ishizaki et aL, 1980;Riddell et aL, 1980;Tawara et aL, 1981) who used the more appropriate within-subject comparison (table II). On the other hand, using a similar study design, both Aro et aL (1982) and Hallengren et aL (1982) reported a significant increase in clearance.…”
Section: Pharmacokinetics Of Propranolol In Hyperthyroidism After Orasupporting
confidence: 59%
See 2 more Smart Citations
“…However, the effect of hyperthyroidism on the clearance of single oral doses of propranolol is less clear. As indicated above, the earlier studies of Bell et aL (1977) and Rubenfeld et aL (1978) did not detect any change, and indeed this has also been the conclusion of a number of other workers (Ishizaki et aL, 1980;Riddell et aL, 1980;Tawara et aL, 1981) who used the more appropriate within-subject comparison (table II). On the other hand, using a similar study design, both Aro et aL (1982) and Hallengren et aL (1982) reported a significant increase in clearance.…”
Section: Pharmacokinetics Of Propranolol In Hyperthyroidism After Orasupporting
confidence: 59%
“…However, few details were given and some of the levels reported are at the lower level of sensitivity of the propranolol assay. Japanese workers (lshizaki et aL, 1980;Tawara et aL, 1981) using single doses of 40 to 80mg detected no change. There was a small but insignificant increase in clearance following propranolol 100mg in the study by Riddell et aL (1980), while Hallengren et aL (1982) and Aro et aL (1982) using 80 and 160mg, respectively, reported a significant increase in clearance as did the studies using long term administration.…”
Section: Pharmacokinetics Of Propranolol In Hyperthyroidism After Oramentioning
confidence: 96%
See 1 more Smart Citation
“…In order to evaluate the relative contribution of the different actions to the overall pharmacological effect, many authors have studied the enantiomers separately, both in experimental (Anlezark et al, 1979;Jaillon et al, 1980) and clinical situations (Tyrer & Lader, 1974;Stensrud & Sjaastad, 1976). Concomitantly the pharmacokinetics (George et al, 1972;Kawashima & Ishikawa, 1980;Tawara et al, 1981;Jackman et al, 1981;Silber et al, 1982) and the metabolism (von Bahr et al, 1982) of the two enantiomers have been studied.…”
Section: Introductionmentioning
confidence: 99%